POLEMIK PENGEMBANGAN DAN PEMBANGUNAN PARIWISATA BERKELANJUTAN BERBASIS KEARIFAN LOKAL DI BALI (STUDI KASUS DI DESA JATILUWIH, KABUPATEN TABANAN) - Wulan Kencana, Ni Made Dharma; Sastra Wijaya, Komang Adi; Dwi Wismayanti, Kadek Wiwin (CITIZEN CHARTER, 2019)
ABSTRACT The implementation of local wisdom-based tourism is the development and development of sustainable tourism that pays attention to the sustainability of the culture that lives in the community and the quality of the environment and in order to increase prosperity and prosperity of the people. The research objective to be achieved is to obtain an actual picture of the polemics that occur in the development process and development of local wisdom-based sustainable tourism in Jatiluwih Village. This study uses descriptive qualitative methods with data collection techniques in the form of interviews, observation, and documentation. The indicators used to dissect the results of the research are the theory of sustainable tourism and the concept of tri hita karana. The results of this study indicate that the implementation of tourism in Jatiluwih Village has been running but has not been optimal. Keywords : Organization of Tourism, Sustainable Tourism, Local Wisdom, Jatiluwih Tourism.